Polyvinyl alcohol fiber reinforced concrete and manufacturing method thereof
By using polyvinyl alcohol fibers and modified materials in concrete, combined with composite cement and composite aggregate, the problems of poor toughness and low compressive strength of concrete in complex stress and harsh environments are solved, and its durability and safety are significantly improved.
Patent Information
- Application Number
- CN202510223698.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-27
AI Technical Summary
Existing concrete has problems such as poor toughness, low compressive strength and easy cracking under complex stress and harsh environmental conditions, which affects its durability and safety.
Polyvinyl alcohol fiber reinforced concrete is used to control the stirring time and conditions to improve the compressive strength, flexural strength and split tensile strength of the concrete by combining composite cement, composite aggregate, modified water reducing agent, modification reinforcement, self-healing capsule and polyvinyl alcohol fiber.
It significantly improves the compressive strength, flexural strength and split tensile strength of concrete, enhances its durability and safety, and solves the problem of prone to cracking of traditional concrete.
Smart Images

Figure CN119683947A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to polyvinyl alcohol fiber reinforced concrete and a preparation method thereof. Background Art
[0002] Concrete is the most commonly used raw material in the fields of construction and municipal engineering. With the development of construction engineering and infrastructure, people have begun to have higher requirements for the performance of traditional concrete. Although ordinary concrete has the advantage of high compressive strength, its disadvantages such as low tensile strength and easy cracking are gradually becoming prominent. Under some complex stress and harsh environmental conditions, its durability and safety are also challenged; although reinforced concrete can avoid the increase of brittleness of ordinary concrete and effectively improve the problem of poor toughness of ordinary concrete, its cracking strength has not been improved. The cracked concrete makes the steel bars lose protection and rust, which seriously affects the durability of reinforced concrete structures.
[0003] In order to adapt to the development of the industry, people began to try to add various materials to concrete to improve the safety, durability and earthquake resistance of the structure. In this process, fiber materials began to be introduced. In the early 20th century, some researchers tried to add steel fibers to concrete, which was an early exploration of fiber-reinforced concrete. The addition of steel fibers improved the tensile strength and crack resistance of concrete to a certain extent, but due to the limited understanding of material properties and processing technology at the time, the effect was not very ideal. The workability and construction performance of concrete after adding steel fibers became worse, and the steel fibers were prone to agglomeration, affecting the uniformity of concrete.
[0004] With the continuous emergence of various new fiber materials, in addition to steel fibers, glass fibers, polypropylene fibers and other materials have begun to appear, and the performance characteristics and application scope of different fiber materials have been further explored. Among them, polyvinyl alcohol fiber reinforced concrete has also been developed. Polyvinyl alcohol fiber has good adhesion and crack resistance, and has shown good application prospects in some structures that require high crack resistance and toughness, but at the same time, it also has problems of low compressive strength and poor toughness.
[0005] Therefore, today's concrete still has the disadvantages of poor toughness, low compressive strength and easy cracking, which leads to poor durability of concrete after construction and limits its use in industry.
[0006] Therefore, a polyvinyl alcohol fiber reinforced concrete and a preparation method thereof are proposed. Summary of the invention
[0007] The purpose of the present invention is to design a polyvinyl alcohol fiber reinforced concrete and a method for making the same. The synthetic raw materials of the present invention include composite cement, composite aggregate, polyvinyl alcohol fiber, modified water reducer, modified reinforcing agent, self-repairing capsule and deionized water. The present invention first combines composite cement and composite aggregate and controls the stirring time to improve the compressive strength of concrete; then adds the prepared modified water reducer and modified reinforcing agent to improve the flexural strength of concrete; then prepares self-repairing capsules and synergizes with the modified reinforcing agent to improve the density and compressive strength of concrete; finally, polyvinyl alcohol fiber is introduced to synergize with composite cement to improve the splitting tensile strength of concrete, so that the durability of concrete is improved.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] In one aspect, the present invention provides a polyvinyl alcohol fiber reinforced concrete, which comprises the following components in parts by weight: Composite cement: 600-700 parts; deionized water: 200 parts; composite aggregate: 150-190 parts; polyvinyl alcohol fiber: 46-50 parts; modified water reducer: 11-15 parts; modified reinforcing agent: 5-7 parts; self-repairing capsule: 3-7 parts; Composite cements include Portland cement, sand, silica fume and fly ash; The polyvinyl alcohol fiber includes polyvinyl alcohol chips and diatomaceous earth; Modified water reducers include calcium lignin sulfonate and styrene; The modified reinforcing agent includes nano calcium carbonate and γ-glycidyloxypropyl trimethoxysilane; The self-healing capsules include methyl methacrylate and sodium alginate.
[0010] Preferably, the composite aggregate is a mixture of limestone particles and basalt particles, the weight ratio of the limestone particles to the basalt particles is 3:2, the particle size of the limestone particles is 15mm-19mm, and the particle size of the basalt particles is 6mm-8mm.
[0011] Another aspect of the present invention provides a method for preparing polyvinyl alcohol fiber reinforced concrete, the preparation method comprising: S1: 600-700 parts of composite cement, 150-190 parts of composite aggregate and 150 parts of deionized water are stirred and mixed at a stirring speed of 800 rpm for a stirring time of 50 min-70 min to obtain cement slurry; S2: Put cement slurry, 11-15 parts of modified water reducing agent, 5-7 parts of modified reinforcing agent, 3-7 parts of self-repairing capsules and 50 parts of deionized water into a mixer, and stir at a speed of 1100 rpm for 70 min-90 min to obtain a mixed slurry; S3: adding 46-50 parts of polyvinyl alcohol fibers into the mixed slurry, and continuing to stir at a speed of 900 rpm for 50 min-90 min to obtain a concrete slurry; S4 pours the concrete slurry into the mold, and after molding, sprays water for curing at a temperature of 24°C and a humidity of 60%, and obtains polyvinyl alcohol fiber reinforced concrete after 7 days.
[0012] Preferably, the preparation method of the composite cement in S1 is: put silicate cement, sand, silica fume and fly ash into a grinder according to the weight ratio, use deionized water as the medium, grind for 2h-4h, and obtain the composite cement after drying; the weight ratio is 6-10:6:2:1.
[0013] Preferably, the preparation method of the modified water-reducing agent in S2 is: 5-9 parts of calcium lignin sulfonate and 20 parts of deionized water are placed in a three-necked flask, and stirred at 80°C for 30 minutes to form a solution A; 1 part of styrene is dissolved in 5 parts of acetone to form a solution B; 1 part of potassium persulfate is dissolved in 5 parts of deionized water to form a solution C; solution B is added dropwise to solution A during heating and stirring, and the dropping time is 20 minutes to obtain a solution D; then solution C is added dropwise to solution D, and the dropping time is 60 minutes to 80 minutes, and the reaction is continued for 6 hours to obtain a solution E; solution E is centrifuged, washed, and dried to obtain a modified water-reducing agent.
[0014] Preferably, the preparation method of the modified enhancer in S2 is: 6-8 parts of nano-calcium carbonate and 6 parts of nano-titanium dioxide are mixed to obtain mixture A; mixture A is placed in an oven and dried at 60°C for 6 hours to obtain mixture B; 1 part of γ-glycidyloxypropyltrimethoxysilane is dissolved in 6 parts of ethanol to obtain mixture C; mixture B is slowly added to mixture C, and stirred at 60°C-80°C for 90 minutes to obtain mixture D; mixture D is centrifuged and washed, and then vacuum dried for 12 hours to obtain a modified enhancer.
[0015] Preferably, the preparation method of the self-healing capsule in S2 is: dissolve 0.6 parts of sodium alginate in 10 parts of deionized water to obtain a sodium alginate aqueous solution; dissolve 1 part of calcium chloride in 15 parts of deionized water to obtain a calcium chloride aqueous solution; slowly add 3-5 parts of methyl methacrylate to the sodium alginate aqueous solution under stirring conditions, the stirring speed is 500rpm, and then continue stirring for 10min-20min to obtain a uniform emulsion; use a syringe to add the uniform emulsion dropwise to the calcium chloride aqueous solution, and then soak in the calcium chloride aqueous solution for 2h to obtain a microcapsule precursor; wash the microcapsule precursor with deionized water, collect the microcapsules by centrifugation, and obtain self-healing capsules after drying.
[0016] Preferably, the preparation method of the polyvinyl alcohol fiber in S3 is as follows: 0.5 parts of tetraethyl orthosilicate is dissolved in 5 parts of ethanol to obtain a diluted solution; 8-10 parts of ground diatomaceous earth are dispersed in 10 parts of ethanol, the diluted solution is added, and the mixture is stirred at 450 rpm for 50 minutes to obtain a precursor solution; the precursor solution is centrifuged, washed, and dried to obtain substance A; 6-8 parts of polyvinyl alcohol slices are dissolved in 40 parts of deionized water, and the mixture is stirred at 95°C for 3 hours to obtain a polyvinyl alcohol solution; the polyvinyl alcohol solution is cooled to 60°C, and 0.5 parts of sodium dodecyl sulfate, 0.5 parts of zinc dialkyl dithiocarbamate and substance A were added, and stirring was continued for 90 minutes to obtain a spinning solution; the spinning solution was filtered and dried, and then spun into fibers, the spinning speed was 30m / min, and the fiber diameter was 10μm-20μm; the fiber was stretched once, the temperature of the first stretching was 150℃, the stretching multiple was 4 times, and then the fiber was stretched twice, the temperature of the second stretching was 100℃, the stretching multiple was 2 times, and the polyvinyl alcohol fiber was obtained after cutting.
[0017] Preferably, the molecular weight of the polyvinyl alcohol slice is 30,000.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention first combines composite cement and composite aggregate and controls the mixing time to improve the compressive strength of concrete. Portland cement, sand, silica fume and fly ash are mixed according to the weight ratio. Portland cement, as the main cementitious material, provides a basic strength foundation. Sand, as a fine aggregate, plays a role in skeleton filling. Silica fume and fly ash work together with Portland cement to form a more compact particle stacking system, thereby improving the compressive strength. After large particles of limestone and small particles of basalt are mixed to form composite aggregates, there are certain gaps between the large particles of limestone, and the small particles of basalt can fill these gaps, making the aggregates more densely stacked; limestone, as the main skeleton material, provides overall structural support, and small particles of basalt are like "reinforcement points". They work together to improve the compressive strength of concrete. Composite cement can also fill the tiny gaps between composite aggregates, making the internal structure of concrete denser and improving the compressive strength.
[0020] 2. The present invention then adds the prepared modified water-reducing agent and modified reinforcing agent to improve the flexural strength of concrete. The modified water-reducing agent prepared by grafting modification has better dispersibility, which can make composite cement and composite aggregate more evenly dispersed and reduce agglomeration. During the modification process, ammonium persulfate is thermally decomposed to generate sulfate radicals, which attack the β-O-4 aromatic ether bond or the carbon atom adjacent to the phenolic hydroxyl group in the lignin sulfonate molecule, extract hydrogen atoms to generate lignin macromolecular free radicals, and styrene containing vinyl double bonds combines with lignin macromolecular free radicals to grow polystyrene side chains on the lignin skeleton. The rigid benzene ring structure of the polystyrene side chain forms an adsorption layer with a thickness of ≥3nm on the surface of cement particles, which prevents particles from approaching through a steric repulsion effect. This adsorption layer can also effectively transmit stress and improve the flexural strength. The coupling agent modified reinforcing agent can improve the compatibility of the reinforcing agent with the concrete matrix. The coupling agent can act as a "bridge" between the reinforcing agent and the concrete matrix. One end of it is combined with the active group on the surface of the reinforcing agent, and the other end is combined with the surface of the concrete matrix, effectively sharing the stress, thereby improving the flexural strength. The modified water-reducing agent and the modified reinforcing agent can work together to optimize the interfacial stress transfer inside the concrete. The modified water-reducing agent makes the components evenly dispersed and improves the state of the composite cement-composite aggregate interface, providing a good foundation for stress transfer. After the modified reinforcing agent is evenly distributed in the concrete and well bonded to the matrix, it can better share and transfer stress when the concrete is subjected to bending stress.
[0021] 3. The present invention improves the density and compressive strength of concrete by preparing self-repairing capsules and synergizing with modified reinforcing agents. During the concrete mixing process, the self-repairing capsules synthesized using methyl methacrylate can adapt to the extrusion of surrounding particles without breaking, maintaining their function of filling gaps. When synergizing with modified reinforcing agents, the self-repairing capsules can form a tighter filling system together with the modified reinforcing agents. When concrete is subjected to external pressure and cracks occur, the self-repairing capsules break and release the internal repair agent. The repair agent can fill the cracks, undergo a curing reaction at the cracks, and reconnect the concrete parts on both sides of the cracks, which is equivalent to rebuilding the compressive structure inside the concrete. When synergizing with modified reinforcing agents, this repair effect is more significant.
[0022] 4. The present invention finally introduces polyvinyl alcohol fiber to synergize with composite cement to improve the splitting tensile strength of concrete. Polyvinyl alcohol fiber has high tensile strength. When microcracks appear, polyvinyl alcohol fiber can cross the cracks and play a role in bridging the cracks. The hydration products generated by the components in the composite cement (such as silica fume and fly ash) during the hydration process can fill the gap between the polyvinyl alcohol fiber and the concrete matrix, thereby enhancing the bonding between the polyvinyl alcohol fiber and the matrix. Polyvinyl alcohol fiber can effectively disperse stress in concrete. When concrete is subjected to splitting tensile force, stress will be transmitted between the fiber and the matrix, and the polyvinyl alcohol fiber will not break immediately, but can continue to withstand a certain tensile force, so that the concrete has a certain ductility during the destruction process; composite cement makes the concrete matrix more compact, and its internal porosity is reduced, which is conducive to the transmission of stress inside the matrix. At the same time, the components in the composite cement interact with the polyvinyl alcohol fiber, further optimizing the stress transmission path, thereby improving the splitting tensile strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a graph of the compressive strength of Example 34 and Comparative Examples 10-12 of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Specific reference Figure 1 The present invention provides a polyvinyl alcohol fiber reinforced concrete and a method for making the same. The technical solution is as follows:
[0026] Example 1
[0027] Preparation of composite cement: Put silicate cement, sand, silica fume and fly ash into a grinder according to the weight ratio, use deionized water as the medium, grind for 2 hours, and obtain composite cement after drying; the weight ratio is 6:6:2:1.
[0028] The composite aggregate is a mixture of limestone particles and basalt particles, the weight ratio of the limestone particles to the basalt particles is 3:2, the particle size of the limestone particles is 15 mm, and the particle size of the basalt particles is 6 mm.
[0029] Preparation of modified water reducing agent: 5 parts of calcium lignin sulfonate and 20 parts of deionized water were put into a three-necked flask and stirred at 80°C for 30 minutes to form a solution A; 1 part of styrene was dissolved in 5 parts of acetone to form a solution B; 1 part of potassium persulfate was dissolved in 5 parts of deionized water to form a solution C; solution B was added dropwise to solution A during heating and stirring for 20 minutes to obtain a solution D; then solution C was added dropwise to solution D for 60 minutes, and the reaction was continued for 6 hours to obtain a solution E; solution E was centrifuged, washed and dried to obtain a modified water reducer.
[0030] Preparation of modified reinforcing agent: Mix 6 parts of nano calcium carbonate and 6 parts of nano titanium dioxide to obtain mixture A; put mixture A into an oven and dry it at 60°C for 6 hours to obtain mixture B; dissolve 1 part of γ-glycidyloxypropyltrimethoxysilane in 6 parts of ethanol to obtain mixture C; slowly add mixture B into mixture C, stir at 60°C for 90 minutes to obtain mixture D; centrifuge and wash mixture D, and then vacuum dry it for 12 hours to obtain a modified enhancer.
[0031] Preparation of self-healing capsules: 0.6 parts of sodium alginate are dissolved in 10 parts of deionized water to obtain a sodium alginate aqueous solution; 1 part of calcium chloride is dissolved in 15 parts of deionized water to obtain a calcium chloride aqueous solution; 3 parts of methyl methacrylate are slowly added to the sodium alginate aqueous solution under stirring conditions, the stirring speed is 500 rpm, and then stirring is continued for 10 minutes to obtain a uniform emulsion; the uniform emulsion is added dropwise to the calcium chloride aqueous solution using a syringe, and then immersed in the calcium chloride aqueous solution for 2 hours to obtain a microcapsule precursor; the microcapsule precursor is washed with deionized water, and the microcapsules are collected by centrifugation, and self-healing capsules are obtained after drying.
[0032] Preparation of polyvinyl alcohol fibers: Dissolve 0.5 parts of tetraethyl orthosilicate in 5 parts of ethanol to obtain a diluted solution; disperse 8 parts of ground diatomaceous earth in 10 parts of ethanol, add the diluted solution, and stir at 450 rpm for 50 minutes to obtain a precursor solution; centrifuge, wash, and dry the precursor solution to obtain substance A; dissolve 6 parts of polyvinyl alcohol slices in 40 parts of deionized water, and stir at 95°C for 3 hours to obtain a polyvinyl alcohol solution; cool the polyvinyl alcohol solution to 60°C, add 0.5 parts of sodium dodecyl sulfate, 0.5 parts of zinc dialkyl dithiocarbamate and substance A, and continue stirring for 90 minutes to obtain a spinning solution; filter and dry the spinning solution, then spin it to form fibers, the spinning speed is 30m / min, and the fiber diameter is 10μm; stretch the fiber once, the temperature of the first stretching is 150°C, the multiple of the first stretching is 4 times, then stretch it twice, the temperature of the second stretching is 100°C, the multiple of the second stretching is 2 times, and the polyvinyl alcohol fiber is obtained after cutting.
[0033] Making polyvinyl alcohol fiber reinforced concrete: S1: 600 parts of composite cement, 150 parts of composite aggregate and 150 parts of deionized water are stirred and mixed at a stirring speed of 800 rpm for 50 min to obtain cement slurry; S2: Put cement slurry, 11 parts of modified water reducing agent, 5 parts of modified reinforcing agent, 3 parts of self-repairing capsules and 50 parts of deionized water into a mixer, and stir at a speed of 1100 rpm for 70 minutes to obtain a mixed slurry; S3: adding 46 parts of polyvinyl alcohol fibers into the mixed slurry, and stirring at a rotation speed of 900 rpm for 50 minutes to obtain a concrete slurry; S4 pours the concrete slurry into the mold, and after molding, sprays water for curing at a temperature of 24°C and a humidity of 60%, and obtains polyvinyl alcohol fiber reinforced concrete after 7 days.
[0034] Example 2-11 Referring to the parameter conditions in Example 1, the specific differences are shown in Table 1.
[0035] Table 1 Parameter conditions of Examples 1-11
[0036] Comparative Example 1 The parameters and conditions in Example 1 are referred to, except that the composite cement is not ground.
[0037] Comparative Example 2 The parameters and conditions in Example 1 are referred to, except that only silicate cement is used as the base cement.
[0038] Comparative Example 3 The parameters and conditions in Example 1 are referred to, except that the weight ratio of Portland cement, sand, silica fume and fly ash is 1:1:1:1.
[0039] Comparative Example 4 The parameters and conditions in Example 1 are referred to, except that the particle size of the basalt particles in the composite aggregate is 17 mm.
[0040] Comparative Example 5 The parameters and conditions in Example 1 are referred to, except that the particle size of the limestone particles in the composite aggregate is 7 mm.
[0041] Example 12 Compressive Strength Test According to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the compressive strength of Examples 1-11 and Comparative Examples 1-5 was tested, and the results are shown in Table 2.
[0042] Table 2 Compressive strength test of Examples 1-11 and Comparative Examples 1-5
[0043] It can be found from Table 2 that in Examples 1-5 and Comparative Examples 1-3, the compressive strength of the comparative examples is relatively low. When the mixture is not ground, the particle sizes of the various components are different, and these materials with different particle sizes are difficult to fully mix evenly. During the concrete preparation process, this will lead to an uneven internal structure of the concrete, thereby affecting the compressive strength of the concrete; when only silicate cement is used as the base cement, the structure formed after hardening is relatively simple, lacking filling and skeleton auxiliary materials such as sand, silica fume and fly ash, and the compressive strength will be significantly reduced; when the weight ratio of silicate cement, sand, silica fume and fly ash is 1:1:1:1, due to the silica fume It has a large specific surface area and high activity. It consumes more water during the concrete hardening process. The hydration reaction inside the concrete is more intense. After the water is lost, the shrinkage stress generated can easily cause cracks on the concrete surface. In the embodiment, silicate cement is used as the main cementitious material to provide a basic strength foundation. Sand is used as fine aggregate to play the role of skeleton filling. Silica fume and fly ash work together with silicate cement to form a more compact particle stacking system. This synergistic effect makes the porosity of concrete continuously reduce during the entire hardening process, thereby effectively improving the compressive strength of the concrete. The compressive strength of Example 4 at 28d is 54.5MPa. In Examples 6-11 and Comparative Examples 4-5, when all large-particle aggregates are used, the compressive strength of the concrete will be significantly reduced due to the increase in porosity and loose particle stacking. When subjected to pressure, the stress is mainly transmitted through the contact points between the aggregates. When only large-particle aggregates are used, the contact points are relatively small and the pores are more, and the stress concentration phenomenon will be more serious; when all small-particle aggregates are used, due to the lack of a stable skeleton formed by large particles, the small particles are prone to move and rearrange when subjected to pressure, thereby reducing the compressive strength; in the embodiment, large-particle limestone and small-particle basalt are mixed to form a composite aggregate, Coarse and fine particles can fill gaps between each other. There are certain gaps between large particles of limestone, and small particles of basalt can fill these gaps, making the aggregates more densely packed. This densely packed state reduces the total volume of pores inside the concrete, thereby increasing the density of the concrete and increasing the compressive strength. By controlling the stirring time, the composite cement and composite aggregate are mixed more evenly. The composite cement can fill the tiny gaps between the composite aggregates and make the internal structure of the concrete denser. The two can work synergistically to jointly improve the compressive strength. The compressive strength of Example 10 at 28d is 59.1MPa.
[0044] Examples 13-24 Referring to the parameter conditions in Example 10, the difference lies in that the preparation parameters of the modified water reducing agent and the modified reinforcing agent and the amount of the composite aggregate are changed. The specific differences are shown in Table 3.
[0045] Table 3 Parameter conditions of Example 10 and Examples 13-24
[0046] Comparative Example 6 The parameters and conditions in Example 10 were referred to, except that the calcium lignin sulfonate was not grafted and modified.
[0047] Comparative Example 7 The parameters and conditions in Example 10 were used with the exception that no modified water reducing agent was added.
[0048] Comparative Example 8 The parameters and conditions in Example 10 are referred to, except that the nano-calcium carbonate is not modified with a coupling agent.
[0049] Comparative Example 9 The parameters and conditions in Example 10 were the same, except that no composite aggregate was added.
[0050] Example 25 Flexural Strength Test According to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the flexural strength of Example 10, Examples 13-24 and Comparative Examples 6-9 were tested, and the results are shown in Table 4.
[0051] Table 4 Flexural strength test of Example 10, Examples 13-24 and Comparative Examples 6-9
[0052] It can be found from Table 4 that in Example 10, Examples 13-18 and Comparative Examples 6-7, when calcium lignin sulfonate is not grafted and modified, the flexural strength of the concrete is low, indicating that a single water reducer cannot significantly improve the flexural strength of the concrete; when the modified water reducer is not added, the flexural strength is reduced, indicating that the modified water reducer is an indispensable part of the concrete; in the examples, the grafted modified water reducer has better dispersibility, it can make the components more evenly dispersed in the concrete, reduce agglomeration, and can be adsorbed on the surface of composite cement and composite aggregate to improve the bonding performance of the composite cement-composite aggregate interface, the active groups in the molecular structure of the grafted modified water reducer can react chemically with the cement and aggregate surfaces to form a stronger interface layer, thereby improving the flexural strength and increasing the durability of the concrete. In Examples 19-22 and Comparative Example 8, when the nano calcium carbonate is not modified with a coupling agent, the flexural strength of Comparative Example 8 is low and the durability of the concrete cannot be guaranteed; in the examples, the coupling agent-modified reinforcing agent can improve the compatibility of the modified reinforcing agent with the composite aggregate, and the coupling agent in the modified reinforcing agent can act as a "bridge" between the reinforcing agent and the composite aggregate, with one end of the coupling agent combining with the active group on the surface of the reinforcing agent and the other end combining with the surface of the composite aggregate, making the combination between the two closer, thereby improving the flexural strength. In Examples 23-24 and Comparative Example 9, when no composite aggregate is added, the flexural resistance of the concrete is limited. When subjected to bending force, cracks easily appear and the concrete is quickly destroyed, resulting in a significant reduction in the durability of the concrete. In the examples, the amount of the composite aggregate is controlled, and a synergistic effect can occur between the composite aggregate and the modified water-reducing agent and the modified reinforcing agent. The modified water-reducing agent and the modified reinforcing agent can work together to optimize the interfacial stress transfer inside the concrete. The modified water-reducing agent makes the composite aggregate particles evenly dispersed and improves the state of the interface, providing a good foundation for stress transfer. After the modified reinforcing agent is evenly distributed in the concrete and well bonded with the composite aggregate, it can better share and transfer stress when the concrete is subjected to bending stress.
[0053] Examples 26-35 refer to the parameter conditions in Example 23, except that the amounts of the modifying reinforcing agent and the self-repairing capsules, the preparation parameters of the self-repairing capsules and the stirring time in S2 are changed. The specific differences are shown in Table 5.
[0054] Table 5 Parameter conditions of Example 23 and Examples 26-35
[0055] Comparative Example 10 The parameters and conditions in Example 23 were the same, except that no modifying and reinforcing agent was added.
[0056] Comparative Example 11 The parameters and conditions in Example 23 were referred to, except that only methyl methacrylate was added as a repairing agent.
[0057] Comparative Example 12 The parameters and conditions in Example 23 are referred to, except that the self-repairing capsules are not added.
[0058] Example 36 Density and compressive strength test According to GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the density of Example 23, Examples 26-35 and Comparative Examples 10-12 was tested. According to GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", the compressive strength of Example 34 and Comparative Examples 10-12 was tested. Figure 1 As shown, the 28d compressive strength test was carried out again 24 hours after the test, and the results are shown in Table 6.
[0059] Table 6 Density and compressive strength test of Example 23, Examples 26-35 and Comparative Examples 10-12
[0060] From Table 6 and Figure 1It can be found that in Example 23, Examples 26-27 and Comparative Example 10, when the modifying and reinforcing agent is not added, the internal structure of the concrete may have more defects and pores, and a tight compressive skeleton cannot be formed, and the density and compressive strength will decrease; in the embodiments, the modifying and reinforcing agent itself can improve the particle stacking state inside the concrete, and they can be adsorbed on the surface of the composite cement to make the arrangement between the particles more compact, thereby improving the density and compressive strength of the concrete. In Examples 28-33 and Comparative Examples 11-12, when only methyl methacrylate is added, although the density and compressive strength of the concrete can be improved to a certain extent, the self-repairing effect is lacking; when the self-repairing capsules are not added, the density and compressive strength of the concrete decrease, indicating that the self-repairing capsules also have the function of filling gaps; in the embodiments, when the self-repairing capsules are uniformly dispersed in the concrete, they can fill part of the gaps like fine aggregates, thereby increasing the density of the concrete, and the shell of the self-repairing capsules has certain elasticity and toughness. During the concrete mixing process, the capsules can adapt to the extrusion of the surrounding particles without breaking, maintaining their function of filling gaps. When the concrete is subjected to external pressure, the self-repairing capsules break and release the internal repair agent, which can fill the cracks, undergo a curing reaction at the cracks, and reconnect the concrete parts on both sides of the cracks; when synergistically acting with the modified reinforcing agent, the capsules can form a tighter filling system together with the modified reinforcing agent, thereby increasing the density and compressive strength of the concrete and improving durability. In Examples 34-35, the stirring time is controlled to make the cement slurry, the modified water-reducing agent, the modified reinforcing agent and the self-repairing capsules mixed more evenly, and the components can fully exert their synergistic effect. The modified reinforcing agent itself can strengthen the internal structure of the concrete, effectively disperse stress and prevent stress concentration. When working synergistically with the self-repairing capsules, the self-repairing capsules increase the density of the concrete, provide a good matrix environment for the modified reinforcing agent to better play its role, and improve the durability of the concrete. When the concrete has gaps or cracks after the first compressive test, the self-repairing capsule inside plays a role. It releases the internal repair agent to fill the gaps or cracks and reconnect the concrete on both sides of the crack. It can be found from Table 6 that the compressive strength of the embodiment has not decreased significantly, while the compressive strength of Comparative Example 10 is significantly reduced when cracks appear in the concrete due to the absence of a modified reinforcing agent; in Comparative Examples 11-12, a single repair agent or the absence of self-repairing capsules cannot maintain the original compressive strength of the cracked concrete, and the compressive strength shows a significant decrease. This shows that the self-repairing capsule plays an important role in repairing cracks, so that the concrete still maintains a high compressive strength after self-repairing cracks, thereby improving the durability of the concrete.
[0061] Examples 37-48 refer to the parameter conditions in Example 34, except that the amounts of composite cement and polyvinyl alcohol fiber, the preparation parameters of polyvinyl alcohol fiber and the stirring time in S3 are changed. The specific differences are shown in Table 7.
[0062] Table 7 Parameters and conditions of Example 34 and Examples 37-48
[0063] Comparative Example 13 The parameters and conditions in Example 34 were referred to, except that diatomaceous earth was not added during the synthesis of the polyvinyl alcohol fiber.
[0064] Comparative Example 14 The parameters and conditions in Example 34 were the same, except that the diameter of the fiber was 50 μm.
[0065] Comparative Example 15 The parameters and conditions in Example 34 were the same, except that no polyvinyl alcohol fiber was added.
[0066] Example 49 Splitting tensile strength test According to GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", splitting tensile strength tests were performed on Example 34, Examples 37-48 and Comparative Examples 13-15, and the results are shown in Table 8.
[0067] Table 8 Splitting tensile strength test of Example 34, Examples 37-48 and Comparative Examples 13-15
[0068] It can be found from Table 8 that in Example 34 and Examples 37-38, when the amount of composite cement is controlled, the materials in the composite cement can fill the pores between the components during the hydration process, refine the pore size, reduce the porosity of the concrete, and improve the splitting tensile strength. In Examples 39-46 and Comparative Examples 13-15, when diatomaceous earth is not added in the process of synthesizing polyvinyl alcohol fibers, since diatomaceous earth has a high specific surface area and a special porous structure, it can interact with the polyvinyl alcohol molecular chains after being added, play the role of a physical cross-linking point, and enhance the force between the molecular chains. Without the addition of diatomaceous earth, the tensile strength and elongation at break of the fibers may be reduced, and the fibers are prone to breakage; when the diameter of the fibers is relatively large, such as 50 μm, the larger the fiber diameter, the relatively worse its flexibility is, and brittle fracture is prone to occur; when polyvinyl alcohol fibers are not added, the splitting tensile strength of the concrete is significantly reduced, which shows that polyvinyl alcohol fibers are a necessary component in concrete; in the embodiments, when microcracks appear, the polyvinyl alcohol fibers can span the cracks, play the role of bridging the cracks, prevent the further expansion of the cracks, and can effectively disperse stress, dispersing the concentrated stress into the surrounding concrete matrix. In Examples 47-48, the time of the assignment is controlled so that all the components are stirred and mixed evenly to play their roles together. The hydration products generated by the components in the composite cement (such as silica fume and fly ash) during the hydration process can fill the gap between the polyvinyl alcohol fiber and the concrete matrix, and enhance the bonding between the polyvinyl alcohol fiber and the matrix. This synergistic effect enables the internal structure of the concrete to maintain better integrity when subjected to tension, thereby improving the splitting tensile strength. The presence of the composite cement provides a good foundation for the effective transmission of stress. At the same time, the components in the composite cement can interact with the polyvinyl alcohol fiber, further optimizing the stress transmission path. This synergistic effect enables the concrete to better resist deformation during the splitting tensile process, thereby improving the splitting tensile strength and ultimately improving durability.
[0069] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A polyvinyl alcohol fiber reinforced concrete, characterized in that: The polyvinyl alcohol fiber reinforced concrete comprises the following components in parts by weight: Composite cement: 600-700 parts; Deionized water: 200 parts; Composite aggregate: 150-190 parts; Polyvinyl alcohol Fiber: 46-50 parts; modified water reducing agent: 11-15 parts; modified reinforcing agent: 5-7 parts; Self-repair capsules: 3-7 servings; The composite cement comprises silicate cement, sand, silica fume and fly ash; The polyvinyl alcohol fiber comprises polyvinyl alcohol slices and diatomaceous earth; The modified water reducing agent includes calcium lignin sulfonate and styrene; The modified reinforcing agent includes nano calcium carbonate and γ-glycidyloxypropyltrimethoxysilane; The self-repairing capsule comprises methyl methacrylate and sodium alginate.
2. The polyvinyl alcohol fiber reinforced concrete according to claim 1, characterized in that: The composite aggregate is a mixture of limestone particles and basalt particles, the weight ratio of the limestone particles to the basalt particles is 3:2, the particle size of the limestone particles is 15mm-19mm, and the particle size of the basalt particles is 6mm-8mm.
3. A method for preparing polyvinyl alcohol fiber reinforced concrete, characterized in that: The polyvinyl alcohol fiber reinforced concrete according to claim 1 is prepared by: S1: 600-700 parts of composite cement, 150-190 parts of composite aggregate and 150 parts of deionized water are stirred and mixed at a stirring speed of 800 rpm for a stirring time of 50 min-70 min to obtain cement slurry; S2: putting the cement slurry, 11-15 parts of modified water reducing agent, 5-7 parts of modified reinforcing agent, 3-7 parts of self-repairing capsules and 50 parts of deionized water into a mixer, stirring at a speed of 1100 rpm for 70 min-90 min to obtain a mixed slurry; S3: adding 46-50 parts of polyvinyl alcohol fibers into the mixed slurry, and continuing to stir at a speed of 900 rpm for 50 min-90 min to obtain concrete slurry; S4 pours the concrete slurry into a mold, and after molding, sprays water for curing at a temperature of 24° C. and a humidity of 60%, and obtains the polyvinyl alcohol fiber reinforced concrete after 7 days.
4. The method for preparing polyvinyl alcohol fiber reinforced concrete according to claim 3, characterized in that: The preparation method of the composite cement described in S1 is: put silicate cement, sand, silica fume and fly ash into a grinder according to the weight ratio, use deionized water as the medium, grind for 2h-4h, and obtain the composite cement after drying; the weight ratio is 6-10:6:2:
1.
5. The method for preparing polyvinyl alcohol fiber reinforced concrete according to claim 3, characterized in that: The preparation method of the modified water reducing agent in S2 is as follows: 5-9 parts of calcium lignin sulfonate and 20 parts of deionized water are placed in a three-necked flask, and stirred at 80° C. for 30 minutes to form a solution A; 1 part of styrene is dissolved in 5 parts of acetone to form a solution B; 1 part of potassium persulfate is dissolved in 5 parts of deionized water to form a solution C; The solution B is added dropwise to the solution A during heating and stirring, and the dropping time is 20 minutes to obtain a solution D; then the solution C is added dropwise to the solution D, and the dropping time is 60 minutes to 80 minutes, and the reaction is continued for 6 hours to obtain a solution E; the solution E is centrifuged, washed and dried to obtain the modified water reducing agent.
6. The method for preparing polyvinyl alcohol fiber reinforced concrete according to claim 3, characterized in that: The preparation method of the modified enhancer described in S2 is as follows: 6-8 parts of nano-calcium carbonate and 6 parts of nano-titanium dioxide are mixed to obtain a mixture A; the mixture A is placed in an oven and dried at 60°C for 6 hours to obtain a mixture B; 1 part of γ-glycidyloxypropyltrimethoxysilane is dissolved in 6 parts of ethanol to obtain a mixture C; the mixture B is slowly added to the mixture C, and stirred at 60°C-80°C for 90 minutes to obtain a mixture D; the mixture D is centrifugally washed and vacuum dried for 12 hours to obtain the modified enhancer.
7. The method for preparing polyvinyl alcohol fiber reinforced concrete according to claim 3, characterized in that: The preparation method of the self-repairing capsule described in S2 is: dissolve 0.6 parts of sodium alginate in 10 parts of deionized water to obtain a sodium alginate aqueous solution; dissolve 1 part of calcium chloride in 15 parts of deionized water to obtain a calcium chloride aqueous solution; slowly add 3-5 parts of methyl methacrylate to the sodium alginate aqueous solution under stirring conditions, the stirring speed is 500rpm, and then continue stirring for 10min-20min to obtain a uniform emulsion; use a syringe to add the uniform emulsion dropwise to the calcium chloride aqueous solution, and then soak it in the calcium chloride aqueous solution for 2h to obtain a microcapsule precursor; wash the microcapsule precursor with deionized water, collect the microcapsules by centrifugation, and obtain the self-repairing capsule after drying.
8. The method for preparing polyvinyl alcohol fiber reinforced concrete according to claim 3, characterized in that: The preparation method of the polyvinyl alcohol fiber in S3 is as follows: dissolving 0.5 parts of tetraethyl orthosilicate in 5 parts of ethanol to obtain a diluted solution; dispersing 8-10 parts of ground diatomaceous earth in 10 parts of ethanol, adding the diluted solution, and stirring at 450 rpm for 50 minutes to obtain a precursor solution; centrifuging the precursor solution, washing, and drying to obtain substance A; dissolving 6-8 parts of polyvinyl alcohol slices in 40 parts of deionized water, stirring at 95°C for 3 hours to obtain a polyvinyl alcohol solution; cooling the polyvinyl alcohol solution to 60°C, adding 0.5 parts of dodecane, and stirring at 95°C for 3 hours to obtain a polyvinyl alcohol solution. Sodium alkyl sulfate, 0.5 parts of zinc dialkyl dithiocarbamate and the substance A, continue stirring for 90 minutes to obtain a spinning solution; the spinning solution is filtered and dried, and then spun to form fibers, the spinning speed is 30m / min, and the fiber diameter is 10μm-20μm; the fiber is stretched once, the temperature of the first stretching is 150℃, the multiple of the first stretching is 4 times, and then stretched twice, the temperature of the second stretching is 100℃, the multiple of the second stretching is 2 times, and the polyvinyl alcohol fiber is obtained after cutting.
Citation Information
Patent Citations
Water-environment concrete self-dissolved microcapsule self-repairing system
CN105645802A
Polystyrene microcapsule self-repairing concrete structure and manufacturing method thereof
CN109180044A
Self-repairing concrete and preparation method thereof
CN110240457A
High-strength polyvinyl alcohol fiber reinforced cement-based composite material as well as preparation method and application thereof
CN113045273A
Environment-friendly concrete resistant to chloride ion permeation and preparation method thereof
CN115353334A
Cited By
Functional composite capsule servo fiber for concrete and preparation method
CN120208573A
Waterborne polyurethane capsule, abrasion-resistant concrete and preparation method of abrasion-resistant concrete
CN120399427A
Early strength concrete material for expansion joint anchoring area and preparation method of early strength concrete material
CN121554232A